Downstaging of carcinoma cervix: yet to reach the unreached - Mahadevappa, Kavita; Prasanna, Naveen; Bembalgi, Shobha; Choukimath, Sharanabasav Murugendrayya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: To know the incidence, presenting symptoms and stages of carcinoma cervix in the patients visiting KIMS, Hubli, Karnataka in the year 2014. Methods: This is a prospective cross-sectional study from January 2014 to December 2014 in Karnataka Institute of Medical Sciences, Karnataka. All patients attending the gynaecological OPD were included in the study. After taking detailed history, patients underwent general physical examination, per speculum and pelvic examination. Patients were divided into 3 groups based on the per speculum and pelvic examination. Group 1 – only PAP smear was taken in women with normal cervix. Group 2 – PAP smear, visual inspection of cervix with acetic acid and biopsy was taken in women with abnormal cervix. Group 3 – only Cervical biopsy was taken and clinical staging was done in women with a suspicious cervix. Results: Total of 8053 patients were screened and examined for carcinoma cervix. A total of 14(0.17%) preinvasive lesions and 85(1.05%) invasive lesions were detected. Out of 85 invasive lesions, the most common pathology was squamous cell carcinomas in 78 (91.76%) patients, adenocarcinomas in 6 (7.05%) patients and adenosquamous carcinoma in 1(1.17%) patient. The most common symptoms of carcinoma cervix were WDPV- 48 (56.4%), Irregular vaginal bleeding- 19 (22.3%), postmenopausal bleeding- 10 (11.7%) and in advanced cases, VVF – 5 (0.05%), RVF- 1 (0.01%) and Uraemia - 2 (0.02%). Most of the patients examined were having disease in stage III -51 (60%) cases, stage IV – 26 (30.58%) cases, stage I -5 (5.8%) cases and stage II – 3 (3.52%) cases. Conclusions: Approximately one in every 100 patients examined in OPD, turned out to be a case of carcinoma cervix, out of which more than 90% patients were diagnosed to be in advanced stage. This huge burden of cases raises the question about screening of carcinoma cervix in rural areas, which needs to be improved. Hence lot has to be done than said, so that screening program of cancer cervix reaches the unreached.